The Effects of Digital Competence, Digital Culture, and Digital Stress on Students’ Academic Performance in Biology Education - Jumeiliani Sirin; Indryani; Ahmad Syarif; Robi Hendra (Indonesian Technology and Education Journal, 2026)
The development of digital technology has brought significant changes in the learning process, including in Biology learning at the secondary education level. This study aims to analyze the influence of Digital Competence, Digital Culture and Digital Stress on the Academic Performance of Biology of high school students. This study uses a quantitative approach with an explanatory research design and cross-sectional methods. Data was collected from 350 high school students through a five-point Likert scale-based structured questionnaire. Data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS 4 software. The results show that digital competence has a positive and significant effect on academic performance in Biology, as well as a positive effect on digital stress. In contrast, digital culture does not have a significant effect on either academic performance or digital stress. Furthermore, digital stress was found to have a positive and significant effect on academic performance, indicating that a certain level of digital stress may enhance students’ engagement in learning activities. These findings suggest that while digital competence plays a key role in improving academic outcomes, it should be accompanied by effective digital stress management. The results of this research are expected to be a reference for educators and curriculum developers in designing productive and sustainable technology-based Biology learning.